Otomatisasi Perangkat Jaringan Komputer Menggunakan Ansible Pada Laboratorium Komputer - M Rifki Affandi; Puspanda Hatta; Agus Efendi (Universitas PGRI Kanjuruhan Malang, 2020)
Network automation is a solution in implementing some complicated or repetitive work. The standard configuration method on network devices performs by entering a network device. That looks easy to configure one or two network devices. that will look not very easy if one must configure many network devices such as routers and servers. Ansible served as a network automation tool on a large and small scale on a computer network, and Ansible served to simplify configuring network devices.